Impact of pay for performance on quality of chronic disease management by social class group in England - Crawley, Danielle (The Royal Society of Medicine, 2009)
OBJECTIVE: To examine associations between social class and achievement of selected national audit targets for coronary heart disease (CHD), diabetes and hypertension in England before and after the introduction of a major pay for performance programme in 2004. DESIGN: Secondary analysis of 2003 and 2006 national survey data for respondents with CHD and diabetes and hypertension. SETTING: England. MAIN OUTCOME MEASURE: Achievement of national audit targets for blood pressure, blood glucose and cholesterol control. RESULTS: There were no significant differences in achievement of blood pressure targets in individuals from manual and non-manual occupational groups with diabetes (2003: 65.9% v 60.3%, 2006: 67.6% v 69.7%) or hypertension (2003: 66.2% v 66.2%, 2006: 72.8% v 71.9%) before or after the introduction of pay for performance. Achievement of the cholesterol target was also similar in individuals from manual and non-manual groups with diabetes (2003: 52.5% v 46.6%, 2006: 68.7% v 70.5%) or CHD (2003: 54.3% v 53.3%, 2006: 68.6% v 71.3%). Differences in achievement of the blood pressure target in CHD [75.8% v 84.5%; AOR 0.44 (0.21-0.90)] were evident between manual and non-manual occupational groups after the introduction of pay for performance. CONCLUSION: The quality of chronic disease management in England was broadly equitable between socioeconomic groups before this major pay for performance programme and remained so after its introduction.